A compact dual frequency microstrip antenna. Issue 6 (25th March 2018) - Chakrabarti, Satyajit
Abstract: In this study, we present a new technique for the development of a dual frequency microstrip antenna. Two identical polarizations at two far apart frequencies have been generated in a compact configuration which uses two elements fed by a single feed line. This design technique provides an independent control to the desired frequencies and reduces element size by 50% compared to the conventional design at the cost of a marginal decrease in gain. The proposed antenna produces dual resonances at 4.056 and 4.96 GHz. It yields impedance bandwidths of about 1.71% at the lower resonance and 1.41% at the higher resonance respectively. It exhibits 7.0 and 6.6 dBi gains at the lower and upper resonances respectively which are 0.3 and 0.7 dB lower than a conventional patch. The measured cross polar discriminations of the proposed antenna are also comparable to the conventional patch. The measured efficiencies are 81.3% and 78.1% respectively.